Seven Diseases as Main Causes of Death In Department of Child Health Dr. Pirngadi General Hospital - Rumiam Silitonga; Lily Emysah; Chairuddin P. Lubis (Indonesian Pediatric Society, 1988)
The retrospective study of main causes of death was conducted in Department of Child Health, Dr. Pirngadi General Hospital, from January to December 1986. Seven diseases as main causes of death were: bronchopneumonia, encephalitis, purulent meningitis, serous meningitis sepsis, tetanus and severe malnutrition with case fatality rates of 29%; 44%; 41%; 31%; 47%; 12% and 18%, respectively.